First wind shear observation in PMSE with the tristatic EISCAT VHF radar - Mann, Ingrid; Häggström, I.; Tjulin, A; Rostami, S; Anyairo, CC; Dalin, P (Journal of Geophysical Research: Space Physics, 2016)
(c) American Geophysical Union, reprinted with permission. Article also available at source: https://doi.org/10.1002/2016JA023080 The Polar Summer Mesosphere has the lowest temperatures that occur in the entire Earth system. Water ice particles below the optically observable size range participate there in the formation of strong radar echoes (Polar Mesospheric Summer Echoes, PMSE). To study PMSE we carried out observations with the European Incoherent Scatter (EISCAT) VHF and EISCAT UHF radar simultaneously from a site near Tromsø (69.58°N, 19.2272°E) and observed VHF backscattering also with the EISCAT receivers in Kiruna (67.86°N, 20.44°E) and Sodankylä (67.36°N, 26.63°E). This is one of the first tristatic measurements with EISCAT VHF, and we therefore describe the observations and geometry in detail. We present observations made on 26 June 2013 from 7:00 to 13:00 h UT where we found similar PMSE patterns with all three VHF receivers and found signs of wind shear in PMSE. The observations suggest that the PMSE contains sublayers that move in different directions horizontally, and this points to Kelvin-Helmholtz instability possibly playing a role in PMSE formation. We find no signs of PMSE in the UHF data. The electron densities that we derive from observed incoherent scatter at UHF are at PMSE altitudes close to the noise level but possibly indicate reduced electron densities directly above the PMSE.